EFEKTIVITAS MEDIA GAMBAR UNTUK MENINGKATKAN PEMAHAMAN SISWA KELAS 3 SD DALAM PEMBELAJARAN IPAS PADA MATERI APAKAH SEMUA HEWAN SAMA - Sari, Mila; Arni, Yusni; Khoirunnisa, Khoirunnisa; Silitonga, Rufita Gracia (JURNAL PENDIDIKAN DASAR PERKHASA: Jurnal Penelitian Pendidikan Dasar, 2026)
This study aimed to determine the effectiveness of picture media in improving third-grade elementary students’ understanding in Science and Social Studies (IPAS) learning. The research used a quantitative approach with a quasi-experimental nonequivalent control group design. The subjects were 40 third-grade students at SDN 30 Palembang, consisting of 20 students in the experimental group and 20 students in the control group. The research instrument was a 10-item multiple-choice comprehension test administered as pretest and posttest. The experimental group was taught using picture media, while the control group used conventional teaching methods. Data were analyzed using an Independent Sample t-test with SPSS. The results showed a significant improvement in the experimental group, with the mean score increasing from 62.50 (pretest) to 86.00 (posttest), while the control group increased from 61.50 to 70.00 (gain 13.82%). The Independent Sample t-test indicated a significant difference between the posttest scores of both groups (p < 0.05), with a t-value of 7.856. In conclusion, picture media is effective in improving third-grade students’ understanding in IPAS learning, particularly due to its suitability with the concrete operational stage of elementary school students’ cognitive development.